Primary Care Management of Scabies in a Family with Extreme Rurality (International Journal of Medical and Surgical Sciences, 2016)
The dermato parasitosis produced by the Sarcoptes scabiei mite hominis variety, has a population distribution related to overcrowding, poor sanitation, poverty and geo-climatic characteristics. Transmission occurs directly through skin or fomites. In the border town of Liquiñe in the Region de los Rios, Chile, a substantial amount of the population is subject to the above characteristics, with difficult access to digital communication and medical referrals. The incidence of scabies is modified through educational interventions, and local sanitation, as well as early diagnosis and timely treatment thus achieving a substantial change in prevalence. A case report is presented. Female patient, 33 years old presents with excoriated crusted lesions, with papules and pustules following two years of development, initial symptomatic management diagnosis of psoriasis and dermatitis, showed no improvement of the lesions. At the same time the 4 year old daughter of the patient presented with primary lesions similar to baseline characteristics. The child’s lesions presented as vesicles in interdigital space, wrists, periumbilical region and mite grooves compatible with scabies. Permethrin 5% topical treatment was prescribed for the whole family, based on the recommendations of the MINSAL guide management is initiated. At 2 months of treatment therapy onset, complete recovery was achieved following two years of evolution of signs and symptoms. This case review aims to reinforce the ideas of early diagnosis, in both probable index case and contact, and continuing education in the community. Effective and timely treatment, in conjunction with the sociocultural reality of each community, taking into account risk factors, such as seeking medical treatment and abandoning therapy. Furthermore, it is also intended to promote institutional networks for treatment dissemination, counseling by specialists and updated information for each dermatological presentation for the general medicine physician.
Keywords: Sarcoptes scabiei; Permethrin; Ivermectin; Therapeutic